Socio-Economic Status of Fishing Communities in Bangsamoro - Naima G. Pendi (RIRAI Publisher, 2022)
The study evaluated the socioeconomic condition of fishermen in the coastal municipalities in Bangsamoro. The respondents of the study were the beneficiaries of the Integrated Livelihood Assistance Program for the fishing communities. The variables included in this study were the demographic profile of the respondents, the technical assistance and livelihood assistance programs of the Bureau of Fisheries and Aquatic Resources. Frequency count, percent, and mean had been used for the description of the variables of the study, likewise, correlation and regression analysis was used to determine the relationship of the variables of the study. Results revealed that the mean age of the respondents is 42.64 years old; having a family size of 6.39; having 21.79 years for the mean years in fishing; and having an average monthly income of P5, 414.70. As to technical assistance, the fisherfolks were seldom given with technical assistance program. Meanwhile, livelihood assistance was given with moderate support in alleviating their socio-economic condition and the development of the fisherfolks. It was also found out that the fisherfolks have somewhat positive knowledge learned, skills acquired, and attitudes towards the assistance programs in alleviating their socio-economic condition and development. Meanwhile, it was also posted that there is a significant correlation between the knowledge, skills acquired, and attitudes of the fisherfolk and the extent of technical and livelihood assistance programs. Moreover, the knowledge learned, skills acquired and attitudes of the fisherfolks significantly influence their fishing activities.